Manuscript Linking, Comparison, and Visual Annotation with IIIF: A Case Study on Leonardo's Codices. - Cirnigliaro, Giuditta; Robson, Glen (Italianist, 2022)
This article explores the possibility of interrogating and analysing Leonardo da Vinci's codices by means of digital open-source technologies for the visualization, annotation, and presentation of sources and manuscripts. IIIF digitized codices and interoperable technologies offer a ground-breaking methodology in the field of Leonardo studies, that allows the user to simultaneously consult and examine images belonging to various repositories and to investigate the interaction of words and images in his manuscripts. By discussing the advantages and disadvantages of these tools as well as sustainability issues, this study deals with technical information that can guide the reader in working with web technology to carry out practical case studies. Finally, through IIIF exhibit tools, users can view Leonardo's textual and visual annotations in the context of the page, and in relation to the wider assemblages of his leaves, in an engaging and interactive experience.